Parasarcophaga (Liopygia) ruficornis (Diptera:Sarcophagidae): a flesh fly species of medical importance - Suwannayod S. (2014)
Parasarcophaga (Liopygia) ruficornis is a well-known flesh fly species of medical importance, both as a myiasis-producing agent and fly seen in a forensic entomology context. This study performed a comprehensive literature review of this fly species, dealing with morphology, bionomics and medical involvement. Important characteristics used to identify P. ruficornis have been provided for both its third instar and adult for identification purpose in the future.